NUMBER OF FUNGI IN RETICULUM, OMASUM AND ABOMASUM BALI CATTLE BASED ON GEOGRAPHICAL LOCATION - Gupita, Ardhita Nurma; Suarjana, I Gusti Ketut; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana, 2023)
Bali cattle are one of Indonesia's germplasm of large livestock species as a source of animal protein, Bali cattle are very well known for their superiority and their existence must be preserved. The purpose of this study was to determine the number of fungi in the reticulum, omasum and abomasum of Bali cattle based on their geographical location and to determine differences in the number of fungi in the reticulum, omasum and abomasum of Bali cattle in the lowlands and highlands. The research materials used were 32 samples from each of the contents of the reticulum, omasum and abomasum taken from the Pesanggaran slaughterhouse (RPH), Denpasar. The variables studied in this study were the number of fungal microbes found in the reticulum, omasum and abomasum of Bali cattle. The data obtained is displayed descriptively, using a qualitative observational research design with a cross-sectional study design. The mean number of fungi in the reticulum, omasum and abomasum of Bali cattle in the highlands and lowlands were respectively 90,63x105±53,475CFU/g and 51,88x105±13,276 CFU/g ; 70,63x105±32,755 CFU/g and 40,63x105±8,539 CFU/g ; 36,88x105±4,787 CFU/g and 21,88x105±4,031 CFU/g. The results of the independent t test analysis showed that the number of fungi in the reticulum, omasum and abomasum of Bali cattle in the highlands was significantly higher (P<0.05) compared to bali cattle reared in the lowlands. This research requires further research regarding the isolation and characteristics of the fungi in the reticulum, omasum and abomasum of Bali cattle in different plains locations to strengthen the research results both theoretically and practically